The Communication Strategy through Brand Image at Batik House as Batik Educational Tourism of Sidomulyo Jember - Juariyah, Juariyah; Adawiyah, Putri Robiatul; Najmah, Najmah (Universitas Muhammadiyah Jember Press, 2024)
This research purposes to analize the Communication Strategy through Brand Image at Batik House as a Batik Educational Tourism of Sidomulyo”. Sidomulyo tourist village is an educational tourist attraction which has several interesting educational tourist destinations, including Sidomulyo batik tourism. Behind these advantages, all Sidomulyo tourist villages have quite significant problems ranging from internal and external problems. In this research, the researcher aims to find out what brand image strategy is carried out by the management of Sidomulyo tourist village in promoting it as an educational tourism village in Jember. The research method used is a qualitative descriptive research method. The data collection technique was carried out in several stages, namely interviews, observation, surveys and documentation. The data analysis technique is carried out through the stages of data reduction, data presentation, and drawing conclusions. It is hoped that the results of this research will be that the management of Sidomulyo tourist village has implemented an appropriate brand image strategy. As a result, this will create a brand image for Sidomulyo tourist village as an educational tourism village in Jember, East Java. Moreover, there are several appropriate criteria for the four stages of brand image strategy that have been proposed by the Cutlip and Center theory, namely, defining the problem (situation analysis), planning and programming (strategy), taking action, communicating and evaluating the program.